THE INFLUENCE OF UTILIZING BIOLOGICAL MODULE INTEGRATED ISLAMIC SPIRITUAL VALUES BASED ON ARIAS EXCRETION SYSTEM MATERIAL ON THE LEARNING OUTCOMES OF STUDENTS XI CLASS AT SMA NEGERI 6 METRO - Siti Fatimah; HRA Mulyani; Agil Lepiyanto (JURNAL LENTERA [PENDIDIKAN PUSAT PENELITIAN LPPM UM METRO], 2020)
Abstract: Module is a teaching material in its presentation systematically arranged. Teaching materials that have characteristics like this are intended so that students can understand the contents of the material independently so that they do not have to depend on a teacher. That is, the module is used to replace a teacher when the teacher is not in the class. The objective of this research is to determine the influence of the use of integrated biology module based on ARIAS Islamic spiritual values. The research was conducted at SMA N 6 Metro with 25 students who had previously been validated by material experts. This type of research is an experiment using the posttest only control design method. This design uses two groups to be studied. The sample used for experiments as well as control groups were taken randomly from certain populations. The technique of collecting data through posttest. Based on the results of the research, the results of the normality test in the experimental class X2 hit <X2 daf -3.38 <7.81, the control class X2 hit <X2 daf -5.93<7.81 which means H0 is accepted and comes from a population that is normally distributed. Fhit homogeneity test results <Fdaf 1.81 <1.98 H0 accepted means that both populations have homogeneous variances. Hypothesis test results, namely the similarity test two average thit> ttable, 2.02>1.68 H0 rejected and H1 accept means that there are differences in the average learning outcomes of students using modules and printed books. The test of the difference of two averages thit> ttable 2.09> 1.68 H0 is rejected and H1 is accepted, meaning there are differences in average learning outcomes using biological modules integrated with Islamic values based on arias using books. It can be concluded that there is an influence of the utilization of biological modules integrated with Islamic values based on ARIAS on student learning outcomes.Â